Analisis Resiko Operasional pada PT. Bank Sumut Unit Usaha Syariah - Dwi Novaliani Agustin; Fadia Maisya Chairunysa; Ika Seprianti; Nadita Syafrida; Arsyadona Arsyadona (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This article discusses operational risk analysis at PT. Bank Sumut Sharia Business Unit in the context of the growth of the sharia banking industry in Indonesia. With the increasing need for banking services that comply with sharia principles, it is important for banks to understand and manage operational risks that can disrupt the performance and sustainability of their operations. This research aims to identify and evaluate operational risks and provide mitigation recommendations to increase the effectiveness of risk management. It is hoped that with in-depth analysis, PT. Bank Sumut can strengthen its position in the sharia banking industry and provide better services to customers.